Differential susceptibility to effects of maternal sensitivity? A study of candidate plasticity genes. (August 2015) - Belsky, Jay; Newman, Daniel A.; Widaman, Keith F.; Rodkin, Phil; Pluess, Michael; Fraley, R. Chris; Berry, Daniel; Helm, Jonathan L.; Roisman, Glenn I.
Abstract: Here we tested whether there was genetic moderation of effects of early maternal sensitivity on social–emotional and cognitive–linguistic development from early childhood onward and whether any detected Gene × Environment interaction effects proved consistent with differential-susceptibility or diathesis–stress models of Person × Environment interaction ( N = 695). Two new approaches for evaluating models were employed with 12 candidate genes. Whereas maternal sensitivity proved to be a consistent predictor of child functioning across the primary-school years, candidate genes did not show many main effects, nor did they tend to interact with maternal sensitivity/insensitivity. These findings suggest that the developmental benefits of early sensitive mothering and the costs of insensitive mothering look more similar than different across genetically different children in the current sample. Although acknowledgement of this result is important, it is equally important that the generally null Gene × Environment results reported here not be overgeneralized to other samples, other predictors, other outcomes, and other candidate genes.